RETRACTED: Evaluation of simultaneous surgical operations in obesity patients - Galimov Dmitriy; Galimov Oleg; Khanov Vladislav; Sufiyarov Rinat; Ibragimov Tel’man; Vagizova Gul’naz (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001